Intracerebral synthesis of glutamine from hyperpolarized glutamate. Issue 4 (8th November 2016) - Mazuel, Leslie; Schulte, Rolf F.; Cladière, Aurélie; Spéziale, Claudine; Lagrée, Marie; Leremboure, Martin; Jean, Betty; Durif, Franck; Chassain, Carine
Abstract : Purpose: Changes in glutamate (Glu) levels occur in a number of neurodegenerative diseases. We proposed the use of 13 C spectroscopy and the highly amplified signal generated by hyperpolarization to achieve spatial and temporal resolutions adequate for in vivo studies of Glu metabolism in the healthy rat brain. Thus, we investigated uptake of hyperpolarized [1 ‐13C ]Glu after a temporary blood–brain barrier (BBB) disruption protocol and its conversion to glutamine (Gln) in the brain. Methods: [1‐ 13 C]Glu was hyperpolarized using the dynamic nuclear polarization process. A temporary BBB disruption using mannitol allowed hyperpolarized [1‐ 13 C]Glu to reach the brain. Then, hyperpolarized [1‐ 13 C]Glu brain metabolism was observed in vivo by MR spectroscopy experiments at 3T. Products synthesized from [1‐ 13 C]Glu were assigned via liquid chromatography–mass spectrometry. Results: Hyperpolarized [1‐ 13 C]Glu reached 20% ± 2.3% polarization after 90 min. After validation of the BBB disruption protocol, hyperpolarized [1‐ 13 C]Glu (175.4 ppm) was detected inside the rat brain, and the formation of [1‐ 13 C]Gln at 174.9 ppm was also observed. Conclusion: The Gln synthesis from hyperpolarized [1‐ 13 C]Glu can be monitored in vivo in the healthy rat brain after opening the BBB. Magn Reson Med 78:1296–1305, 2017. © 2016 International Society for Magnetic Resonance in Medicine.